Effect of a (La, Sr)2CoO4 Phase on the Oxygen Exchange Reaction of Dense and Porous (La, Sr)CoO3 Electrodes. (3rd May 2017) - Kawada, Tatsuya; Yashiro, Keiji; Hashimoto, Shin-ichi; Amezawa, Koji
Abstract : Promotion of oxygen exchange rate on La0.6 Sr0.4 CoO3- δ (LSC) by the coexistence of the Ruddlesden-Popper phase was investigated for dense film and porous electrodes. Application of a porous (La, Sr)2 CoO4 (LSC214) layer on a dense film electrode increased the reaction rate and decreased the activation energy. The oxygen reaction rate on a bare LSC varied from sample to sample, suggesting strong effect of the surface chemistry such as Sr segregation. On the other hand, the electrode modified with a LSC214 layer showed less dependence. The presence of an LSC214 phase appeared to suppress the Sr segregation, which accounts for the improvement of the reaction rate. In contrast to dense electrodes, porous electrodes showed no significant improvement with addition of LSC214. From the estimation of the effective utilization length, the surface reaction rate of a porous electrode was much higher than that on a dense electrode, which may influence the different effect observed by addition of LSC214 in dense and porous electrodes.